Performance Evaluation of Turtle Excluder Device off Dhamra in Bay of Bengal - Prakash, R. Raghu; Boopendranath, M. R.; Vinod, M. (Fishery Technology, 2025)
Turtles are endangered and protected species under the Indian Wildlife Protection Act 1972. A number of non-target resources, such as sea turtles, are caught during trawling. This study reports the field trials conducted using TED-installed fish trawls in Odisha waters to evaluate the efficacy of TED. The incidence of sea turtles was one for every 15 hauls and the turtle excluder device (CIFT-TED) showed 100% exclusion for the sea turtle entering the trawl system. The exclusion rates were 2.5% for the total catch and 2.7% for the shrimp. Twenty eight species of finfish were encountered during the trials of which 17 were represented in the excluded portion of the catch.